2013
DOI: 10.1039/c3fo60083a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Agave tequilana fructans with different degree of polymerization profiles on the body weight, blood lipids and count of fecal Lactobacilli/Bifidobacteria in obese mice

Abstract: Fructans are dietary fibers with beneficial effects on the gastrointestinal physiology and offer a promising approach for the treatment of some metabolic disorders associated with obesity. In vitro and in vivo studies were developed to test the safety of fructans obtained from Agave tequilana Weber var. azul. Additionally, an in vivo experiment using a diet-induced obesity model was performed to compare the effect of agave fructans with different degree of polymerization (DP) profiles: agave fructans with DP >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 35 publications
(38 reference statements)
2
40
0
1
Order By: Relevance
“…Additional characterization of bacterial crossfeeding via in vitro models and computational simulations will also help advance our understanding of the role of diet on the microbiome. Because rodent studies have provided evidence for the benefits of agave inulin supplementation on body composition, blood cholesterol, and blood glucose concentrations (45)(46)(47), further investigation is warranted to determine whether these effects translate into health benefits in human populations.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additional characterization of bacterial crossfeeding via in vitro models and computational simulations will also help advance our understanding of the role of diet on the microbiome. Because rodent studies have provided evidence for the benefits of agave inulin supplementation on body composition, blood cholesterol, and blood glucose concentrations (45)(46)(47), further investigation is warranted to determine whether these effects translate into health benefits in human populations.…”
Section: Discussionmentioning
confidence: 98%
“…In vitro experimentation has demonstrated that agave inulin is readily fermented by bifidobacteria and lactobacilli (43,44). In addition, rodent studies have provided evidence that the botanical origin and chemical structure of different inulin-type fibers (e.g., agave inulin and chicory inulin) induce variable effects on body composition, blood cholesterol, and blood glucose concentrations (45)(46)(47). The prebiotic effects of agave inulin in healthy adults, however, are currently unknown.…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, earlier investigations showed that mice fed with standard or high fat diet with agavins of low DP led to a body weight loss [10][11][12]. However, the microbial mechanisms remain in unclear [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…However, the microbial mechanisms remain in unclear [12,13]. New molecular techniques that enable analysis of non-cultivable bacteria are starting to be applied in studies investigating the impact of prebiotics on the cecal microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Fructans properties (healthy and technological) are dependent inter alia on the polymerization degree [21,30]. Inulin is the most commonly used in food industry, i.e., as the ingredients of dairy products, because of its prebiotic and also textural properties, bread, biscuits, cereal and meat products [21].…”
Section: Introductionmentioning
confidence: 99%